Abo Blood Groups and Their Relationship to Periodontitis - Marwa Jassim Mohammed; Abdulla Zaidan Khalaf (Scholars Digest Publishing, 2022)
Oral cavity contains many different surfaces colonized by prokaryotic and identified more than 700 species, the tooth decay and gum disease diseases affecting patients and represent the main problem is the most important public health (MacDonald,2015), Periodontitis is a chronic inflammatory disease, in which imbalances occur between host and microbial interactions. This is the key to the onset and development of the disease (Alvarez et al., 2018). Diabetes is one of the most common chronic diseases and in a continuous numerical increase. Diabetes has been defined as a group of metabolic disorders characterized by hyperglycemia caused by defects in insulin secretion, insulin function or both, hyperglycemia leads to The prevalence of multi-system damage, including affecting oral tissues (Cicmil et al., 2018) , In the cases of diabetic patients, the functions of immune cells, including neutrophils, monocytes, macrophages, alteration of commitment, chemical attraction and phlegm, often inhibit sufficient defense against bacteria in the gingival sinus and greatly increase the destruction of the gingival membrane . In diabetics, although neutrophil function is reduced, there may be an excellent response to the cell line of the monocytes / phagocytes when confronted with any bacterial antigens (Kripal, 2017).